Comparison of different methods of controlling pain during debonding of orthodontic brackets - Iqbal, Kashif; Khalid, Zahra; Khan, Ali Akhtar; Jan, Abdullah (Journal of the Pakistan Medical Association, 2023)
Objective: To compare the efficacy of finger pressure and plastic wafers in terms of pain control during debonding. Method: This cross sectional study was conducted at the Department of Orthodontics, Armed Forces Institute of Dentistry, Rawalpindi, Pakistan, from January to June 2020, and comprised patients of either gender aged 13-21 years who had completed fixed orthodontic treatment with 0.022 brackets of Roth prescription and required debonding. The patients was divided into two equal groups. In group A, teeth were stabilised with finger pressure with cotton between the finger and teeth, and then debonding was done using open mouth technique. In group B, teeth were stabilised using a plastic wafer between maxillary and mandibular teeth, and then debonding was done using closed mouth technique. Pain was assessed using a visual analogue scale VAS. Data was analysed using SPSS 23. Results: Of the 110 patients, each of the 2 groups had 55(50%) subjects. Overall, there were 35(32%) males and 75(68%) females. The mean age of the sample was 16±2.4 years. Mean pain scores among the males was 32.0±7.68 compared to 34.067±12.59 among the females (p>0.05). Subjects in group B had significantly less pain than those in group A (p<0.05). Conclusion: Plastic wafer was found to be more effective in terms of controlling pain during debonding compared to finger pressure. Key Words: Pain measurement, Methods of debonding, Orthodontic pain management, Finger pressure, Plastic wafer.